The Impact of Fiscal Balance Funds Toward Human Development in Riau Province - Purba, Samuel Fery; Permatasari, Citra; Mudrawan, Indra; Simandjorang, Bonataon Maruli Timothy Vincent (Jurnal Bina Praja, 2023)
Fiscal decentralization is an effort by the central government to distribute regional development by providing fiscal balance funds to regional governments. The fund aims to promote regional self-sufficiency and community welfare throughout Indonesia. Riau is one of the provinces implementing fiscal balance funds and has high regional income in various sectors. However, the human development of some regions in Riau is unequal, even though the fiscal balance issued by the government continues to increase. This study aims to explore the fiscal balance funds, which consist of revenue sharing funds (DBH), general allocation funds (DAU), special physical allocation funds (DAK Physical), and special non-physical allocation funds (DAK Non-Physical), will affect human development in Riau Province from 2017 to 2022 in terms of health, education, and standard of living. This study used 72 observations from 12 cities/regencies in Riau obtained from Statistics Indonesia, and it was conducted by using a quantitative approach through panel data regression. This study produces three estimation models for each aspect of human development. REM is the model chosen to answer the three research models. The results in the first model showed that DAK Physical and DAK Non-Physical influenced human development in the health aspect. The second model was DAK Non-Physical, which significantly affected human development in education. Finally, DBH, DAU, and DAK Non-Physical significantly affected human development in aspects of decent living standards. Fiscal balance funds affect every aspect of human development in Riau. Fiscal planning and budgeting by local governments in Riau with targeted support are needed to further human development.